Penerapan Model Investigasi Kelompok Dalam Pembelajaran Menulis Argumen Pada Teks Eksposisi Siswa Kelas X Sma Muhammadiyah Padangpanjang - Pohan, Ratna Sari Dewi; Irfadila, Mimi Sri; Syofianti, Lara (Inovasi Pendidikan, 2024)
This research was motivated by an interview conducted with an Indonesian language teacher at SMA Muhammadiyah Padangpanjang. The results revealed that students showed a low interest in writing argumentative exposition texts. The purpose of this study is to describe the improvement of students’ motivation and interest through the implementation of the Group Investigation model in learning to write arguments in exposition texts. This research is a quantitative study using a descriptive method. The research sample consisted of 29 students. The instruments used in this study were interview sheets, observation sheets, student activity questionnaires, and student performance tests. The data were collected through several procedures: (1) observing the learning process using the Group Investigation model, (2) conducting a writing test on argumentation in exposition texts, and (3) distributing student activity questionnaires during the learning process. This model involves group work to conduct research, analysis, and writing arguments within exposition texts. Quantitative methods were used by collecting data from the learning process and the results of group writing activities. Data analysis was conducted through text content analysis, evaluation of group participation, presentation analysis, student reflections, ability improvement analysis, and overall learning evaluation. Based on the data analysis using questionnaires, the average score obtained was 69.03. The quantitative analysis showed that the average score of students’ ability to write arguments in exposition texts using the Group Investigation model reached 98.85, which is categorized as very good. The hypothesis testing showed that the calculated t-value (1.6944) was greater than the t-table value (1.6341), indicating that the hypothesis was accepted. Therefore, it can be concluded that there is a significant difference in students’ learning outcomes in writing argumentative exposition texts. Students were highly enthusiastic and active in group interactions, as reflected in their discussions and group presentations.Keywords: Group Investigation Model; Argumentative Writing; Exposition Text; Learning Motivation; Cooperative Learning